Les féministes et l’université américaine - Malie Montagutelli (Revue LISA)
This paper focuses on feminine and feminist issues within the context of American universities and their curricula. After a brief survey of the progress made by women in higher education since the 1960s, it will focus on the actions of feminists during the same period. It attempts to determine their impact on higher education then and now and ends by pointing to the extreme diversity of views being expressed today by women in general and by feminists on American campuses, a diversity which may prove to be detrimental to their further progress.